2006
DOI: 10.1007/s10100-006-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

On the role of heterogeneous and imperfect information in a laboratory financial market

Abstract: Asset market, Experimental study, Asymmetric information, Information support,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…As to the second result, consistently with the findings of Alfarano et al (2006) -who showed that more information in the market has some effects on trading volume and price volatility -we found that the divergence between the market price and the asset's fundamental value is systematically smaller when the rating agency is present.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As to the second result, consistently with the findings of Alfarano et al (2006) -who showed that more information in the market has some effects on trading volume and price volatility -we found that the divergence between the market price and the asset's fundamental value is systematically smaller when the rating agency is present.…”
Section: Resultssupporting
confidence: 90%
“…By means of a laboratory experiment, we investigate the effect and interaction between private and public information. Previous experiments showed that lemmings behaviour can survive in a market context where information is private (Hey and Morone, 2004), and that an experimental market can be very volatile and not efficient in transmitting information (Alfarano et al, 2006). We study experimentally, if socially undesirable behaviour -that survives in a market contestmay be eliminated owing to the presence of rating agencies.…”
mentioning
confidence: 94%
“…Different from empirical studies, experimental economists generate a laboratory-based financial market to explore information availability and trader effectiveness [2]. In particular, [31] created five markets to address the dissemination and aggregation of information, concluding that markets follow rational expectation equilibrium model predictions.…”
Section: Related Workmentioning
confidence: 99%
“…To prove the efficient market hypothesis (EMH) [14], many researchers have been devoted to studying the impact of the information on the movement of stock markets [2,3,7,16,21,23,28,29,38,41,48]. One of the earliest reports, that by Cutler et al [10], found that macroeconomic performance news could explain approximately one-third of the variance in stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…10 Except in the first session in which, due to technical reasons, program stopped in scenario 30. 11 The risk attitude test used was the same as that used in Alfarano et al (2006). Participants face a sequential choice between a risky and a sure option in 11 scenarios, were the risky option is kept constant and the sure option starts from a low value and sequentially increases.…”
mentioning
confidence: 99%